Treatment of insomnia in elderly patients - Kneginja RICHTER (Journal for ReAttach Therapy and Developmental Diversities, 2020)
Introduction: Insomnia is one of the most common health conditions amongst the elderly population. It causes suffering and numerous health problems for those affected. Objectives: To review published results of common non-pharmacological and pharmacological interventions of insomnia and to discuss their application in older patient groups. Methods: We conducted a systematic literature review for the topic non-pharmacological treatment of Insomnia in Elderly and non-systematic review on the topic of pharmacological treatment using the electronic databases PubMed, PsycInfo, Google Scholar and Web of Knowledge. Only published articles and reviews were included. Results: Sleep education can support the onset of sleep. As a simple and side-effect-free measure, sleep education should be offered to all elderly individuals with sleep-onset insomnia including those living in retirement homes. Stimulus control means that the bed or the bedroom should only be visited, if there is sufficient tiredness, or left, when tiredness is not sufficient, which is very challenging and sometimes impossible due to the decreasing mobility of the elderly, especially under treatment with hypnotics. Sleep restriction can be conducted in a moderate way, reducing the time spent in bed every week for 30 minutes. Light therapy supports the regulation of the circadian body rhythm by exposing the patients to bright artificial light during the day. As a simple measure with only a few side effects, it is suitable when treating elderly individuals in institutions. Digital therapies are an emerging trend in the treatment of sleep disorders and require further empirical investigation of their effectiveness in the treatment of insomnia in the elderly. Non-pharmacological therapy should be the first-line therapy according to guidelines. Prescribing of sleep medication should take into account the period of time until the maximum effective level is reached, the half-life of the preparation, the binding behaviour to receptors and the metabolism of the preparation, which is especially relevant for elderly populations due to polypharmacy. Conclusion and implications: A modified, short cognitive behavioural therapy for insomnia combined with light therapy is the treatment of choice for elderly patients. However, a short-term pharmacological therapy is recommended as a temporary solution to immediately reduce high levels of distress. It is suggested to integrate both therapeutic approaches into a comprehensive therapeutic concept for insomnia in elderly people.